Eksplorasi Konsep Waktu Salat Dalam Al-Qur'an Perspektif Ilmu Falak - Sheila Nur Alifah; Maloko, Thahir (HISABUNA: Jurnal Ilmu Falak, 2024)
“This research discusses the exploration of the concept of prayer times in the Al-Qur'an from a astronomical perspective. This research is library research which collects data from books, journals and other reference sources. This research uses a sharia approach to analyze Islamic legal norms regarding prayer times, as well as an astronomical approach to determine prayer times based on the position of celestial bodies. The research results show that first, the verses of the Koran provide guidance regarding natural signs, such as the rising and setting of the sun, which are used in determining prayer times. The prayer times mentioned in the Qur'an have a scientific basis that can be measured and calculated using the reckoning method. Second, astronomy, with its arithmetic method, allows accurate prayer times to be determined based on the position of the sun, which includes the times of Fajr, Zuhr, Asr, Maghrib and Isha. The implication ot thhis research provides a theoretical contribution in strengthening the understanding that Islamic teachings regarding prayer times have a scientific basis that is acceptable in the context of modern science. Practically, the results of this research can be used as a reference in preparing a more accurate prayer time schedule and in developing technological applications that help Muslims determine prayer times easily and precisely.” Keywords: Eksploration, Falak Science, Prayer Time